Transformation of Islamic Educational Values in Generation Z: Challenges and Opportunities - Nining Khurotul Ain; Noer Rohmah; Mahmoud Mahmoud; Ismail Lutfi Japakiya (SYAMIL: Journal of Islamic Education, 2025)
This research was conducted to analyze the concept of Islamic education, the characteristics of Generation Z, the digital era and its influence on Islamic education, and the transformation of Islamic educational values in Generation Z. This paper uses a qualitative approach. Data were collected through library research. The findings indicate that the Islamic identity of Generation Z is increasingly shaped by digital technology. The transformation of Islamic educational values in this generation influenced by technological development, which alters educational patterns, learning strategies, and the role of social media in transmitting values. Challenges arise in this process, including the dominance of social media, identity crises, lack of role models, and religious education that is less adaptive to modern contexts. Despite these challenges, digitalization also offers valuable opportunities. Technology can support da’wah, the formation of virtual Islamic communities, and the production of creative content that reflects the lifestyle of Generation Z. These methods are effective in instilling Islamic values within the rapid flow of digital information. Moreover, this situation provides an opportunity to strengthen spirituality through technology, which aligns with the goals of Islamic education: to form individuals who are faithful, pious, and noble in character. The core values of Islamic education, moral, intellectual, remain vital in shaping holistic individuals who can contribute positively to society. Adaptations such as digital learning materials, online and hybrid models, and social media as educational platforms demonstrate the urgency of digital transformation to ensure Islamic education remains relevant to the future needs of Generation Z.